(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Ganga-Yamuna Doab is prevalently agricultural and weight of over expanding populace has made imbalance in agriculture development and levels of pay in provincial agrarian culture. So as to limit the regional imbalances, to improve salary and expectations for everyday comforts of individuals, independence in food grains and accomplishment of equivalent open doors it would be of incredible centrality if the Ganga-Yamuna Doab is partitioned into classifications of crop productivity and development levels. It is along these lines important to chalk out a system for a general development of the region. The Ganga-Yamuna Doab is a long and slender portion of land between two rivers the Ganga making the eastern limit, and the Yamuna circumscribing the west. The Doab reaches out as a wedge from the Siwalik Hills to the intersection of the two streams at Allahabad. The region lies between 250 16’ and 300 35’ North latitudes, and 770 5’, and 820 21’ East longitudes, and spreads a zone of around 58400 sq, km. The Doab is around 832 km. long from northwest to southeast course, while its width differs around 64 to 112 km.